Development of Snatch Theft Security System - Azhar, Nur Alis; Mohamad Zakaria, Anis Zakiah (2016)
This project titled is “Development of Snatch Theft Security System” is focused on how the connection between transmitter and receiver in the Arduino sim900a with GSM Module. The GSM stands for Global System for Mobile communications. This is a global standard which is followed by the GSM modules inside the cellular phones which enables them to be connected with any mobile network around the globe. In certain applications the microcontroller based systems has to be connected with the GSM network which will enable a user to control the system by sending messages or making a call. The systems can also send messages to the user to alert or inform about the status of the system running. In all such cases a separate GSM module is used rather than using the mobile phones. The advantage of using a GSM communication with a system or device is that the user can control the system wirelessly no matter how far it is kept compared to any other wireless communication, provided that both the user and the device should be in a cellular coverage area. A GSM modem is a specialized type of modem which accepts a SIM card, and operates over a subscription to a mobile operator, just like a mobile phone. From the mobile operator perspective, a GSM modem looks just like a mobile phone. When a GSM modem is connected to a computer, this allows the computer to use the GSM modem to communicate over the mobile network. While these GSM modems are most frequently used to provide mobile internet connectivity, sending and receiving SMS and MMS messages. It is needed to be used in this project to send and receive SMS from the GPS tracker to obtain the location of stolen item.